Cartilaginous Choristoma in Tonsil : A Rare entity - Sharma, Sujan; Makaju, Ramesh; Shrestha, Bikash (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
Choristoma is a tumor like mass consisting of tissues foreign to the site at which they are located. We report a 39-year-old female who presented to our out-patient department with history of pain and burning sensation in the throat. On examination of the tonsils, bilateral keratosis was present. Histological examination demonstrated the unexpected presence of mature hyaline cartilage surrounded by lymphoid follicles. DOI: http://dx.doi.org/10.3126/acclm.v1i1.12316 Ann. Clin. Chem. & Lab. Med. 1(1) 2015: 49-50